Analisis Terhadap Penegakan Hukum Pemilu Dalam Perspektif Undang-Undang Nomor 7 Tahun 2017 di Indonesia: Penegakan Hukum Pemilu - Vanessa Octavia (Ilmu Hukum Prima (IHP), 2019)
Abstract The title of this is article is "Analysis of Election Law Enforcement in the Perspective of Law Number 7 of 2017" The main problem we raised is how the Electoral Commission faces changes to Law No. 15 of 2011 concerning election administrators and Law Number 8 of 2012 concerning the election of DPR, DPD and DPRD Members into Law Number 7 of 2017 and what are the challenges faced by Electoral Commission in the Implementation of Laws Number 7 of 2017. In this paper the method we used is juridical normative analytical that gives an overview of an object through certain analytical techniques. The ways that can be done by the KPU in dealing with changes to Law Number 15 Year 2011 concerning election administrators and Law Number 8 of 2012 concerning the election of DPR, DPD and DPRD Members become Law Number 7 Year 2017. Something that can be made are involving electoral institutions, which in this case is the Election Supervisory Body and its ranks. Therefore, Election Supervisory Body must increase strict supervision in the administration of elections. Keywords: How to deal with changing laws, Challenges faced by the Electoral Commission, Law Number 7 of 2017